PROSES PERENCANAAN ANGGARAN BERBASIS KINERJA PADA POLITEKNIK PEMBANGUNAN PERTANIAN MALANG - adhi, kuncoro; Hakim, Abdul; Makmur, Mochmamad (Profit: Jurnal Adminsitrasi Bisnis, 2019)
Â This study aims to describe and analyze the performance-based budget planning process at Malang Agricultural Development Polytechnic. This study uses a qualitative descriptive approach with data collection techniques through observation, interviews, and documentation. The results of this study indicate that the planning process carried out by Malang Polbangtan refers to the stages outlined in the National Development Planning System which consists of the preparation of plans, determination of plans, control of the implementation of the plan, and evaluation of the implementation of the plan. At the planning stage, the input used in the preparation is still a rough estimate based on trends and has not been supported by valid data. As a result, changes to what was planned in the implementation of the plan were often carried out. Control and evaluation has not been supported by the existence of internal policies that in writing provide guidance in determining the performance indicators of each program or activity that has been planned, so that in determining the performance achievements of the program and activities activities are hampered, because performance indicators are not performance oriented